Aktifitas Kunyit (Curcuma domestica Val.) Sebagai Antiinflamasi Ditinjau Dari Berbagai Literatur - Humaira Fadhilah; Karunia Rachmani; Nurihardianti Hajaring (STIKes Kharisma Persada, 2021)
Inflammation is a normal protective response to tissue injury caused by physical trauma, damaging chemicals, or microbiological substances. Steroids and nonsteroidal anti-inflammatory drugs have many side effects, so there are many anti-inflammatory developments originating from natural ingredients, especially in plants. Plants that are scientifically proven to have anti-inflammatory properties, namely turmeric (Curcuma domestica Val.) The method used in this literature study is a review of various journals published online, with the keyword turmeric as an anti-inflammatory, reviewed one by one and then the journals obtained are collected and information created by summarizing the content and then comparing the journals to be used as references. The results showed that turmeric tested had anti-inflammatory activity. The strength of the anti-inflammatory effect is shown by the carrageenan induction method which inhibits endema in rat feet and inflammation in the liver using the method of induction by diethylnitrosamine in this plant varies, depending on the dose. Compounds that are considered to provide anti-inflammatory activity are curcumin class compounds because they can inhibit the formation of prostagladin, thromboxan, and prostagycycline by inhibiting the activity of the cyclooxygenase enzyme. Curcumin also inhibits the formation of leuketrien compounds by inhibiting the activity of the lipoxygenase enzyme.